TEACHING READING COMPREHENSION TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI 12 PALEMBANG BY USING STORY PYRAMID - Mawadda Mawadda (Edukasi, 2015)
The aim of this study was to find out whether or not there is a significant difference on students’ reading comprehension achievement taught  using story pyramid strategy than those who are taught using teachers’ method strategy. The study used quasi-experimental design using nonequivalent pretest posttest design. The investigation of population of this study was all of the eighth grade student  of SMPN 12 Palembang in the academic year 2013/2014, which consist of 80 students coming from two classes. The sample of this study were class VIII.2 consisting of 40 students was treated as experimental group and VIII.1 consisting of 40 students was treated as control group, which selected using convenience sampling. This study was conducted for about one month. In finding a significant difference of students’ reading comprehension average score from pretest to posttest taught using Story Pyramid Strategy, the writer conducted using Independent Sample T-Test. The data was collected in form of pretest and posttest of students reading comprehension scores. Then, it was analyzed using independent sample t-test to meet the objective of the study. From the result analysis, it was found that there was a significant difference in posttest score on the students’ reading comprehension achievement taught using story pyramid strategy since the p-output was lower than 0.05.